2013
DOI: 10.1038/srep02981
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Mellitus and the Risk of Hepatitis C Virus Infection: A systematic review

Abstract: The aim of this study was to evaluate the relationship between type 2 diabetes mellitus (T2DM) and hepatitis C virus (HCV) infection and to examine whether T2DM enhances the risk of HCV infection compared with the risk in the general population. We followed standard guidelines to perform a meta-analysis. The associated literature was selected based on the established inclusion criteria. The summary odds ratio (OR) and 95% confidence interval (95% CI) were used to investigate the strength of the association. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 52 publications
4
50
0
6
Order By: Relevance
“…Similar results were reported in a case-control study, 12.6 % patients with non-cirrhotic HCV had T2DM and the prevalence of T2DM was significantly higher than in non-cirrhotic HBV patients (4.9 %) [9]. Besides, patients with T2DM had a higher risk of HCV infection compared with non-T2DM patients [10].…”
Section: Introductionsupporting
confidence: 85%
“…Similar results were reported in a case-control study, 12.6 % patients with non-cirrhotic HCV had T2DM and the prevalence of T2DM was significantly higher than in non-cirrhotic HBV patients (4.9 %) [9]. Besides, patients with T2DM had a higher risk of HCV infection compared with non-T2DM patients [10].…”
Section: Introductionsupporting
confidence: 85%
“…Several researchers observed diabetes mellitus more frequently in patients with genotype 2a HCV (Mason, 1999) and advanced liver fibrosis (Papatheodoridis, 2006). At the same time, some authors have found that patients with diabetes mellitus are more susceptible to infection by hepatitis C virus (Guo, 2013). Other researchers suppose that HCV serves as a trigger in the development of type 1 diabetes in susceptible persons.…”
Section: Resultsmentioning
confidence: 99%
“…Another study of people enrolled in a community‐based cohort in the US showed that HCV infection increased the risk of developing diabetes [adjusted hazard ratio (HR), 11.6; 95% CI 1.4–96.6], but only among those at high risk of diabetes (based on body mass index and age) . Finally, a recent meta‐analysis suggested, on the basis of limited evidence, that having diabetes can also be a risk factor for contracting HCV .…”
Section: Introductionmentioning
confidence: 99%
“…6], but only among those at high risk of diabetes (based on body mass index and age) [11]. Finally, a recent meta-analysis suggested, on the basis of limited evidence, that having diabetes can also be a risk factor for contracting HCV [12].…”
Section: Introductionmentioning
confidence: 99%